Maintaining Physical Fitness Through Cardiovascular Exercise Models: Literature Review - Widodo, Haryo; Wiriawan, Oce; Wijono, Wijono (STRADA : Jurnal Ilmiah Kesehatan, 2021)
This study aims to conduct a literature review on maintaining physical fitness through cardiovascular exercise. This study used a literature review method with a focus on cardiovascular exercise to maintain health from previous studies. A selection of literature comes from national or international journals on safe google scholar, science direct, and research gate with the publication period 2010-2021 and keyword searches for cardiovascular exercise / cardiovascular endurance or cardiovascular training to improve physical fitness. The journal review technique uses a synthesis matrix by creating a table consisting of columns of reference sources, samples, methods, interventions, and findings. The results in this study were adapted as many as 13 reviewed articles. The conclusion in this study is that there are many kinds of cardiovascular exercise. Which various types of cardiovascular exercise can actually maintain and even improve physical fitness